Two new species of Nyctelia Latreille (Coleoptera: Tenebrionidae) from Argentinean Patagonia with zoogeographical and ecological remarks - Flores, Gustavo E.; Cheli, Germán H. (Zootaxa, 2014)
Two new species of the genus Nyctelia Latreille (Pimeliinae: Nycteliini) from Argentinean Patagonia, N. sulcogranata sp. nov. and N. recteplicata sp. nov., are described. Distributional maps, habitus, photographs and illustrations of genitalic features for these two new species are included, with comparisons to other known species of the genus. A discussion is presented on distributional habitat records and biogeography.